Whether aortic valve repairs are a reasonable substitute for replacement in children? EXPERT REVIEW - Abdurakhmanov, Z. M.; Varbanets, S. V.; Yemets, I. N. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Literature review analysis is accomplished relating to the alternativeness of aortic valve (AoV) repairs in children of various ages with AoV disease. Long- and midterm results of AoV repairs in children both with severe aortic regurgitation and aortic stenosis are outlined. Several advantages and feasibility of AoV repairs over aortic valve replacement accentuating on the individualization of surgical repair strategy to the age of the patient, durability of the repair depending on material properties, growth potential and geometry of AoV are substantiated.